2022
DOI: 10.1101/2022.09.02.22279522
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sodium content of menu items in New York City chain restaurants following enforcement of the sodium warning icon rule, 2015-2017

Abstract: In 2016, New York City (NYC) began enforcing a sodium warning regulation at chain restaurants, requiring placement of an icon next to any menu item containing >=2,300 mg sodium. As menu labeling may improve menu nutritional composition, we investigated whether sodium content of menu items changed following enforcement of the sodium warning icon. All menu offerings at 10 quick-service (QSR) and 3 full-service (FSR) chain restaurants were photographed in 2015 (baseline) and 2017 (follow-up) and matched to nut… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Further, QSR purchases were made during lunchtime hours (12–3 pm), while FSR purchases were made during dinnertime hours (5–9 pm). Additionally, the sodium warning icon may have less utility at QSR in general due to fewer items meeting the 2,300 mg requirement, as Sisti et al found in the accompanying menu evaluation [ 22 ], and as was found in the present study, where we excluded two QSR chains because of low or no warning icon presence. However, if sodium warning icons are ubiquitous on a restaurant’s menu, as it the case in some FSR chain restaurants, then they may also be less impactful, as consumers will have few lower-sodium alternatives.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Further, QSR purchases were made during lunchtime hours (12–3 pm), while FSR purchases were made during dinnertime hours (5–9 pm). Additionally, the sodium warning icon may have less utility at QSR in general due to fewer items meeting the 2,300 mg requirement, as Sisti et al found in the accompanying menu evaluation [ 22 ], and as was found in the present study, where we excluded two QSR chains because of low or no warning icon presence. However, if sodium warning icons are ubiquitous on a restaurant’s menu, as it the case in some FSR chain restaurants, then they may also be less impactful, as consumers will have few lower-sodium alternatives.…”
Section: Discussionmentioning
confidence: 48%
“…While efforts like nutrient warnings aim to foster transparency about the food supply and may contribute to health-promoting behaviors [ 25 ], commercial factors such as excessive marketing, targeted marketing, and unhealthy food offerings can strongly influence health [ 26 ]. The accompanying menu evaluation by Sisti et al found no reduction in high-sodium offerings at chain restaurants approximately one year following implementation of the sodium warning icon [ 22 ]; it may take additional time and action to reduce sodium in restaurant foods. Recently, the US Food and Drug Administration released voluntary sodium reduction goals for the food industry [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a modest decline in sodium content across packaged food categories was observed soon after the launch of NSRI [ 33 ], it was lower than the goal that was set (7% compared with 25%) and a recent evaluation showed that industry reduction of sodium did not continue to decrease beyond 2014 [ 34 ]. A separate evaluation showed that the number of high-sodium menu items did not decrease 1 y after implementation of the sodium icon warning [ 35 ]. We also found that a third of participants reported that they looked for sodium information at least most of the time suggesting awareness regarding sodium in some of the NYC adult population.…”
Section: Discussionmentioning
confidence: 99%